Rancangan Bangun CRM Operasional Penerimaan Mahasiswa Pada Prodi Kesehatan Di Kampus STIKES Hakli - Aprilla, Kartika Trisya; Suhari, Yohanes (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In the era of globalization, the use of information technology has become increasingly important, especially in higher education. STIKES Hakli faces the need to enhance its new student admission process to address intense competition and high expectations from prospective students regarding access and information. Implementing a Customer Relationship Management (CRM) system is considered an effective solution. This study aims to design and implement an operational CRM system to improve the efficiency and effectiveness of the new student admission process at the Health Study Program of STIKES Hakli. Utilizing Extreme Programming (XP) methods and a qualitative approach, the research designs a CRM subsystem that includes Login for secure access, digital Registration with validation, automated Selection with real-time dashboards, and Data Verification for accuracy. The system also features transparent Announcement of selection results, secure Data Management, and Communication and Support with FAQs and support channels. The study's results indicate that the implementation of the operational CRM system enhances efficiency by accelerating data processing and accuracy, simplifies data management, improves interactions between prospective students and the institution, and increases satisfaction with the services provided, thereby positively contributing to the new student admission process.